Pharmaceutical care and intervention for intubated patients in an Intensive Care Unit (ICU) (Research, Society and Development, 2021)
Intensive Care Unit (ICU) is understood as a hospital wing for the care of critical patients who are in a moderate to severe clinical condition and who need technological devices and a team that assists them throughout the hospitalization period. The main objective is to report the importance of pharmaceutical care and intervention to patients who are intubated in the ICU, as well as to understand the methodology of mechanical ventilation, as well as to signal factors that justify the relevance of submitting the pharmaceutical professional to the team that constitutes the ICU. As a research method, bibliographic research was carried out, an article was selected through health journals, such as the Medical Literature Analysis and Retrieval System (Medline) and SCIELO, using the following descriptors: Pharmaceutical Assistance, Artificial Respiration and Intensive Care Units. The research found that there are several factors that justify the reason for the insertion of the pharmacist in the ICU, among them: ensuring the rational use of medicines, adhering to the best means of administration, checking the possible existence of drug interactions, among others. Finally, it is concluded with the present research that each health professional has its importance in the treatment of patients, and together they can do more than good care, but offer a better quality of life to these patients.